1996
DOI: 10.1074/jbc.271.37.22624
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure, Neural-specific Expression, and Chromosomal Localization of , a Second Murine Homeobox Gene Related to

Abstract: The cut locus of Drosophila encodes a diverged homeodomain-containing protein that is required for the development of external sensory (es) organs and other tissues. A homologous gene (Cux-1) that encodes a transcriptional repressor has been identified in the mouse and other mammals. We have identified a second murine homeobox-containing gene (designated Cux-2) that is structurally related to Drosophila cut. The murine Cux-2 homeobox was similar to Drosophila cut and encoded a homeodomain that contained a char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 35 publications
0
76
0
1
Order By: Relevance
“…In brief, Cux-2 protein is nuclear and is expressed only in neurons (Quaggin et al, 1996). The spatiotemporal patterns of Cux-1 and Cux-2 IR overlapped entirely that of gene expression ( Fig.…”
Section: Cux-1 and Cux-2 Protein Expressionmentioning
confidence: 80%
“…In brief, Cux-2 protein is nuclear and is expressed only in neurons (Quaggin et al, 1996). The spatiotemporal patterns of Cux-1 and Cux-2 IR overlapped entirely that of gene expression ( Fig.…”
Section: Cux-1 and Cux-2 Protein Expressionmentioning
confidence: 80%
“…In humans, two Cux genes, CUX1 [14] and CUX2 [15], have been identified. Studies in mice showed that Cux1 was expressed in many somatic tissues and also in the brain [16], whereas expression of Cux2 was restricted to neural tissue [17].…”
Section: Discussionmentioning
confidence: 99%
“…Of scription factor with three novel DNA-binding domains, the genes that were identified through these screens, the termed CUT repeats (Blochlinger et al 1988; Andres BTB-domain zinc-finger gene longitudinals lacking (lola) et al 1994; Moon et al 2000). Vertebrate cut homologs, and several genes encoding subunits of the Brahma chroincluding mouse Cux1 and Cux2 (Valarche et al 1993; matin-remodeling complexes were investigated further Quaggin et al 1996;Zimmer et al 2004) and human with regard to their interaction with cut during wing-CDP (Neufeld et al 1992), are postulated to regulate margin development. The genetic interactions between cell growth and terminal differentiation.…”
mentioning
confidence: 99%